THE EFFECT OF DISCOVERY LEARNING MODEL TOWARDS BIOLOGY PROBLEM SOLVING - Intan Novalia Putri Utami (Journal Of Biology Education Research (JBER), 2021)
This research was a Quasy research experiment. This study aimed to determine the differences in Problem Solving Abilities (KPM) using Discovery Learning models and Conventional learning models. The study was conducted in March-October 2018. The population in this study was class X in one of the private high schools in Bogor Regency 2017/2018 academic year. The sampling technique uses purposive sampling techniques. The sample for the experimental class was class X MIPA B treated by using the Discovery Learning learning model with a total of 40 students and class X MIPA A being treated using a conventional learning model with 40 students with instruments to solved problems (KPM). Based on the results of the t test shows that there are differences in problem solving abilities between students who learn to use the Discovery Learning model and Conventional learning models. Discovery Learning class groups are higher than Conventional class groups, this can be seen from the average N-Gain score of problem solving abilities in the Discovery Learning class can be use 50 and Conventional class groups of 42. Therefore, the Discovery Learning learning model used in biodiversity material to improve students' biological problem solving capability.